2017
DOI: 10.3171/2016.8.jns152709
|View full text |Cite
|
Sign up to set email alerts
|

Reoperative endoscopic endonasal surgery for residual or recurrent pituitary adenomas

Abstract: OBJECTIVE Regrowth of the lesion after surgical removal of pituitary adenomas is uncommon unless subtotal resection was originally achieved in the first surgery. Treatment for recurrent tumor can involve surgery or radiotherapy. Locations of residual tumor may vary based on the original approach. The authors evaluated the specific sites of residual or recurrent tumor after different transsphenoidal approaches and describe the surgical outcome of endoscopic endonasal transsphenoidal reoperation. METHODS The aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 65 publications
0
32
0
1
Order By: Relevance
“…reviewed 59 revision pituitary endoscopic surgeries, demonstrating an overall postoperative CSF leak rate of 2.5%. Similarly, Negm et al . reported a 2.4% postoperative CSF leak rate in a retrospective review of 41 endoscopic pituitary surgeries.…”
Section: Complicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…reviewed 59 revision pituitary endoscopic surgeries, demonstrating an overall postoperative CSF leak rate of 2.5%. Similarly, Negm et al . reported a 2.4% postoperative CSF leak rate in a retrospective review of 41 endoscopic pituitary surgeries.…”
Section: Complicationsmentioning
confidence: 99%
“…A total of 15 studies met the inclusion and exclusion criteria . Overall, the evidence level was low with the majority of studies comprising level 4 evidence (Table ).…”
Section: Reconstructionmentioning
confidence: 99%
“…Endoscopic technique is also helpful in recurrent and residual cases. 3 However, there seems pros and cons of both the techniques. We used microsurgical technique in all the cases, except in few where we used both, due to lack of appropriate endoscopes.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, based on 2 studies of 29 and 24 subjects, including patients with functional and nonfunctional tumors, postreoperative regrowth rates were 3.1% and 0%, respectively. 37,38 However, postreoperative observation periods were not sufficiently long, with a median of 17 (range; 12-108) mo in the former and a mean of 39 (range, 3-135) mo in the latter investigation. Most recently, Bakhsheshian et al 39 reported surgical treatment outcomes of 268 NFPA patients with a mean follow-up time of 38 (range, 3-235) mo.…”
Section: Postsalvage Surgery For Recurrent/residual Tumorsmentioning
confidence: 99%